PENGARUH PENYULUHAN DENGAN MENGGUNAKAN MEDIA KOMIK SEBAGAI MEDIA PEMBELJARAN UNTUK MENINGKATKAN PENGETAHUAN PESAN GIZI SEIMBANG (PGS) PADA SISWA KELAS IV - Siti Moz Moza; Hasan Aroni; Sugeng Iwan Setiabudi (Poltekkes Kemenkes Malang, 2019)
School children usually have a habit of eating high calorie foods low in fiber, so it can be susceptible to disease. Elementary school children aged around 7 until 13 years is the second most rapid growth period after toddlers. At that age, discipline and awareness of children are still lacking in maintaining health, namely dental and oral health so vulnerable to caries in the teeth. One age group that often experience the disease problem is the elementary school age group. According to WHO or World Health Organization data, 2013 an increase in dental caries prevalence in the 12 year age group, i.e. 13.7 percent from 28.9 percent in 2007 rose to 42.6 percent in 2013. One way to reduce unhealthy snack habits in children is to provide nutritional education is interesting and easy to understand by children, so the role of educational media is very important, one of which is a comic. The purpose of this research is to know the influence of counseling by using comic media as a learning media to improve knowledge of balanced nutrition message or PGS on fourth grade students SDN KALIREJO 02 And SDN KALIREJO 03 Lawang Malang Regency. This research type is Pre Exprerimental with design of one group pretest post test design and executed from September to December 2017. The number of samples obtained according to inclusion criteria during the research period is 83 samples. The results showed that there was an increase in knowledge. The result of statistical analysis on knowledge obtained p value equal 0,000 is smaller than 0,05. Based on the results of research, the provision of comics can increase knowledge about the habit of toothbrushing. Comic media dpaat accepted as slah one media in the process of nutrition pengajraan not only provide information about nutrition but also able to provide entertainment to students.